LEGAL STUDY ON THE VALIDITY OF AGREEMENTS MADE BASED ON FORGED DOCUMENTS OR LETTERS ACCORDING TO ARTICLE 263 OF THE CRIMINAL CODE - Hasdar; Sunardi Purwanda; Muhammad Sabir Rahman; Bakhtiar Tijjang; Elvi Susanti Syam (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to determine and analyze the legal regulations regarding the crime of forgery of documents or letters as regulated in Article 263 of the Criminal Code in the context of making agreements and a legal analysis of the validity of an agreement made based on forged documents or letters from the perspective of Article 263 of the Criminal Code and Civil Law. This research uses a normative research method with a legislative approach, a conceptual approach, and a comparative approach. The legal sources used are primary, secondary, and tertiary legal materials. The legal analysis will be conducted using a qualitative prescriptive approach. The results of this study are the Legal Regulations regarding the Criminal Act of Forgery of Documents or Letters as regulated in Article 263 of the Criminal Code in the context of making an agreement, namely Article 263 of the Criminal Code is classified as forgery of ordinary or general documents or letters and the criminal sanction is a maximum imprisonment of 6 years and the category of forgery related to agreements according to the provisions of Article 263 of the Criminal Code in legal activities can be in the form of Forgery of the signature of one of the parties in the agreement, Use of a false identity when making an agreement, Forgery of private deeds or authentic deeds (with the note that authentic deeds can also ensnare the notary if proven to be involved or if it involves officials or procedures for making deeds regulated by law) and Changes to the contents of the agreement unilaterally after it is signed and Legal Analysis of the Validity of an Agreement Made Based on Forged Documents or Letters According to the Perspective of Article 263 of the Criminal Code and Civil Law, namely in Article 263 of the Criminal Code does not automatically determine the validity or nullity of the agreement. However, a criminal decision stating that there is forgery of a letter can be used as strong evidence in a civil process to cancel or declare the agreement invalid and declare the invalidity of the forged document or letter regarding the agreement. Meanwhile, in the provisions of Civil Law, if the conditions in Article 1320 of the Civil Code do not comply with the agreement in which there is a forged letter or document, it is invalid and null and void by law, but it is not automatically void and must be canceled and decided by the court.